Turbidite Facies of the Halang Formation in Ajibarang Area, Central Java - Praptisih, Praptisih; Kamtono, Kamtono (Geological Agency, 2011)
DOI: 10.17014/ijog.v6i1.112An understanding of deepwater turbidite sediments is very important mainly dealing with the determination of a reservoir geometry. The problem arising in the turbidite sediment geometry is very complex and varied, and its existence depends on how, when, and type of its environment. In Central Java, the broad turbidite sediment distribution of the Halang Formation is needed to be observed its facies association. This paper will discuss the turbidite facies of Halang Formation in the Ajibarang area. The method used to analyze the turbidite facies is by measuring stratigraphic sections and observing the lithofacies characteristics to reconstruct its depositional environment. The Halang Formation outcrop in the Ajibarang area is dominantly composed of alternating sandstone and claystone or marl. Based on the observation, the turbidite facies of Halang Formation, in the Ajibarang area, was deposited on a submarine fan system at the middle fan of suprafan lobes. Compiling with the previous studies, the source of the Halang Formation is indicated to be derived from the south southwest.